Swiss Programme for Research on Global Issues for Development (r4d pro gramme) - NFP [Nr.] (2018)
Research and innovation are decisive factors for sustainable global de velopment. With their knowledge, skills, experience and worldwide netw ork of partners, researchers can make an important contribution toward s the solution of global problems.